A study of The Rock by T.S. Eliot : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in English at Massey University - Kennedy, D. J (Massey University, 1973)
Chapter I of this thesis is just a brief account of the genesis of The Rock: brief for fear of reproducing what has already been ably said before by Mr E. Martin Browne in his book The Making of T.S. Eliot's Plays. In this section the pageant and music-hall revue, which were the vehicles for this vaguely propagandist work, are treated, and what is so strangely important about the music-hall form of entertainment is that Eliot was very much attracted to it. This chapter, although it just sets the scene, shows the author working at a much more superficial level than ever before. Chapter II deals with the importance of Eliot's socio-religious thinking relative to The Rock in the 1930s. The authoritarian nature and very rigour of his orthodoxy may have been partly the reason why The Rock and After Strange Gods were never republished, but the important point is made clear, through these views on Christian orthodoxy and tradition, that Eliot was to be admired as perhaps the only poet and intellectual of great standing in England in the 1930s who gave his allegiance to something wholly outside himself. In addition, what is made explicit in this chapter, and held implicit throughout, is that Eliot was no turncoat who now gladly and facilely embraced the succour of Mother Church as some critics would have us believe. What is made plain is that this relatively new convert was finding a via media between facile hope and pointless despair - hence the very discipline and rigour of his Anglo-Catholic affirmations. Chapter III is about the requirements of the medium in what was in fact the first time Eliot had moved beyond a coterie audience. The demands and limitations are listed as criteria against which The Rock can only be measured; and although the choruses may be the first bad poetry Eliot had written, it is made clear that he was conscious of the seeming hollowness of ecclesiastical utterances. It may seem paradoxical that Eliot, in this propaganda setting, was actually trying to wring the neck of rhetoric, and the moral is even enforced by his inclusion of a verse-sketch which clearly shows an adulteration through rhetoric. Chapter IV reverberates on the two preceding chapters in its delineation of a return to a purified yet traditional language as well. Although the nobility of language from biblical books is still there, Eliot was for the first time using a democratic, and non-hieratic, language of ordinary man. There is a new distrust of the cunning and rhetorical, as contained in the 'objective correlative' of before, and the author is attempting a personal atone through what seems to be an authenticity and sincerity of tone. The Rock could conceivably exist without the choruses at all but they are important, unlike the prose episodes, because they were written without the various collaborators. Chapter V attempts, very briefly, to establish that The Rock was not a propagandist's hackwork but that the author was consciously groping for new forms of prosody and dramatic techniques preparatory to his later plays and poetry and, as such, the work is seen in the perspective of an important stage midway in Eliot's career as an artist and thinker.
Keywords: Eliot, T. S. 1888-1965